(untitled) (TRIM. Tordesillas, revista de investigación multidisciplinar, 2022)
Nudity and sex have been historically repressed categories due to the belief that the body is a work of God and its purity brings us closer to it. Onlyfans is an app that gives access to uncensored content. Since the second half of the 20th century, the paradigm on sexuality inherited from Christianity has been progressively overcome. What was previously seen as something unique (even sacred) through technical reproducibility has been massified and made ordinary. If nudity and sex, in ancient times, were linked to religious acts related to fertility, and then the church brought them back to the intimacy of the heterosexual marriage bed, today the technical media have "uncovered" sex. Here’s how apps like Onlyfans destroy the aura of nudity and sex.